cot 7 4 π cot 7 8 π − cot 7 8 π cot 7 1 2 π − cot 7 1 2 π cot 7 4 π = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Converting it into functions of 7 π , 7 2 π , 7 4 π would make it easier to come to the conclusion, esp for those who already know that
cot α cot β + cot β cot γ + cot γ cot α = 1
α + β + γ = 3π/2
tan(α + β) = tan(3π/2 - γ)
(tanα + tanβ)/(1 - tanαtanβ ) = 1/tanγ
tanαtanβ + tanβtanγ + tanγtanα = 1
cot(4π/7)cot(8π/7)-cot(8π/7)cot(12π/7)-cot(12π/7)cot(4π/7)
= tan(13π/14)tan(5π/14)+tan(5π/14)tan(3π/14)+tan(3π/14)tan(13π/7)
= 1
13π/14 + 5π/14 + 3π/14 = 3π/2
Problem Loading...
Note Loading...
Set Loading...
cot 7 4 π cot 7 8 π − cot 7 8 π cot 7 1 2 π − cot 7 1 2 π cot 7 4 π = cot 7 4 π cot 7 8 π cot 7 1 2 π ( tan 7 1 2 π − tan 7 4 π − tan 7 8 π ) = tan 7 4 π tan 7 8 π tan 7 1 2 π tan 7 1 2 π − tan 7 4 π − tan 7 8 π = − tan 7 4 π tan 7 π tan 7 2 π − tan 7 2 π − tan 7 4 π − tan 7 π = tan 7 π tan 7 2 π tan 7 4 π tan 7 π + tan 7 2 π + tan 7 4 π = 1 See Note
Note: Since 7 π + 7 2 π + 7 4 π = π , angles of a triangle. ⇒ tan 7 π + tan 7 2 π + tan 7 4 π = tan 7 π tan 7 2 π tan 7 4 π